The Development of a Web-Based School Expenditures Budgeting System Using The Agile Method - Jessica Aurelia Sujangga; Ridwan Sanjaya; G. Freddy Koeswoyo (Soegijapranata Catholic University, 2024)
Schools under the auspices of Kanisius Foundation, Surakarta Branch are still making school expenditures budgeting manually using Microsoft Excel application. Thus, all school expenditure budgeting data in each school is not well integrated and the flow of adaptation to each change in Excel format is difficult. If the situation remains like this where the data is not well integrated, then the difficulty will be that the data processing process to obtain information about the school budgeting plan and its reports will become difficult. Meanwhile, the need is for the results of data processing to be used as a basis for decision making quickly and precisely. The development of a web-based school expenditures budgeting system using the Agile method becomes the solution for schools expenditure budgeting plan’s data to be well integrated and to be used as a basis for decision making. This development uses Agile method because this method is flexible to several changes that occur within the development process.